Customer Adoption of Internet Banking: An Empirical Investigation in Taiwanese Banking Context - Chuang, Chao Chao (Information Management and Business Review, 2012)
In these days, banks work hard to attract consumers and keep their market share by providing them with more innovative services through Internet banking. Banking services are now just at the distance of one click from the mouse. The purpose of this paper is to explore how and why specific factors affect adoption of Internet banking in Taiwan context. The findings suggest six identified factors are significant in respect of customers’ adoption of Internet banking services. Convenience, accessibility and feature availability are the main motivators for consumers to use Internet banking service. Results also reveal that security and privacy play important roles in discouraging the customers to use Internet banking services. Conclusions and managerial suggestions are proposed to provide a practical contribution for bank managers to better understand customers’ perception of e-banking service quality and enhance customers’ adoption rates.